Penerapan Gamifikasi Wordwall untuk Menarik Minat Belajar Matematika Siswa pada Materi Pecahan - Frety Isyra' Aini; Andika Setyo B L (JUMAT: Jurnal Matematika, 2025)
The research was conducted to attract students' interest in learning mathematics in fraction material assisted by Wordwall gamification. This research is quantitative research with quantitative descriptive data analysis techniques. The population of this research was MI Nur Nabawiy students with a sample of 23 Class 3 students. The instrument used was a non-test in the form of a questionnaire containing 20 statements about students' interest in learning mathematics after the learning process was carried out with the help of Wordwall gamification. The research results show an overall percentage of 80.4% in the very high category. This research received a positive response from students, indicating that the application of Wordwall gamification can attract students' interest in learning mathematics.